2014
DOI: 10.1111/nph.12784
|View full text |Cite
|
Sign up to set email alerts
|

In vivo assessment by Mach–Zehnder double‐beam interferometry of the invasive force exerted by the Asian soybean rust fungus (Phakopsora pachyrhizi)

Abstract: SummaryAsian soybean rust (Phakopsora pachyrhizi) causes a devastating disease in soybean (Glycine max). We tested the hypothesis that the fungus generates high turgor pressure in its hyaline appressoria to mechanically pierce epidermal cells.Turgor pressure was determined by a microscopic technique, called transmitted light double-beam interference Mach-Zehnder microscopy (MZM), which was developed in the 1960s as a forefront of live cell imaging. We revitalized some original microscopes and equipped them for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…Edwards and Bonde (2011) observed that an appressorium of P. pachyrhizi penetrated the leaf of soybean plants using primarily mechanical force with the aid of digestive enzymes. Chang et al (2014) and Loehrer et al (2014) showed that the turgor pressure formed on the appressorium of P. pachyrhizi was independent of melanin biosynthesis due to the metabolic degradation of products, such as glycerol, inside the appressorium. In the present study, the events of pre-penetration of P. gossypii (uredospore germination until appressorium formation) on cotton plants appeared very similar to those observed for the interaction soybean-P. pachyrhizi.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Edwards and Bonde (2011) observed that an appressorium of P. pachyrhizi penetrated the leaf of soybean plants using primarily mechanical force with the aid of digestive enzymes. Chang et al (2014) and Loehrer et al (2014) showed that the turgor pressure formed on the appressorium of P. pachyrhizi was independent of melanin biosynthesis due to the metabolic degradation of products, such as glycerol, inside the appressorium. In the present study, the events of pre-penetration of P. gossypii (uredospore germination until appressorium formation) on cotton plants appeared very similar to those observed for the interaction soybean-P. pachyrhizi.…”
Section: Resultsmentioning
confidence: 99%
“…According to Vittal et al (2014), the early events of uredospore germination, appressorium formation, and penetration of P. pachyrhizi on the soybean leaf occurred by 24 hai. The formation of appressoria is a pivotal event that allows a number of fungi to penetrate the leaf cuticle and establish a successful infection in their hosts (Chang et al, 2014;Dean, 1997;Loehrer et al, 2014;Ludwig et al, 2014;Mendgen and Deising, 1993). Certain biotrophic and hemibiotrophic fungi, such as those causing powdery mildews and anthracnose, respectively, can directly penetrate the cuticle through the action of cutinases, but in most cases, the strong osmotic pressure exerted by the melanized or not appressoria becomes detrimental (Dean, 1997;Ludwig et al, 2014;Mendgen and Deising, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…The resurgence of Mach–Zehnder double‐beam interferometry now contradicts the paradigm that force‐based penetration of plant cells is restricted to melanized appressoria. By measuring the turgor pressure of Asian soybean rust ( Phakopsora pachyrhizi ) appressoria in vivo , Loehrer and colleagues show that these nonmelanized penetration structures exhibit a pressure close to that of M. oryzae , while being able to penetrate non‐biodegradable membranes even more efficiently ( Loehrer et al ., ).…”
Section: Imagingmentioning
confidence: 97%
“…Several transcriptomic analyses of appressoria formation of urediniospores led to identification of the genes responsible for metabolism and regulation of the cell division cycle, indicating that this structure plays an active role in the penetration process (Hu et al, 2007;Stone et al, 2012;Talhinhas et al, 2014). Urediniospores from the soybean rust fungus directly penetrate their host through the epidermis, in a similar manner to basidiospores of heteroecious fungi, and form an appressorium with a high cell turgor pressure of 5.13 MPa (Loehrer et al, 2014a), which correlates with what has been observed in other fungal plant pathogens (Ryder & Talbot, 2015). However, P. pachyrhizi basidiospores are hyaline and devoid of melanine, indicating a different penetration modality.…”
Section: Early Stages Of Infection: Host Penetration and Haustorium Fmentioning
confidence: 99%